Konsep Etika dalam Bhagavadgita - Ustadi Hamsah (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
As a Hinduism holy script Bhagavadgita was cortained the principle view of faith. In this script, fundamental aspec: of thing always depended to cosmic view manifested in concept of Atman and Brahman, Bhagavadgita explained non-dualistic philosophy as a ground of ethics, namely Isvara (God from Shankara) who had good attitudes (sagunas)